Cryoballoon Ablation Strategy in Persistent Atrial Fibrillation - Straube, Florian; Pongratz, Janis; Kosmalla, Alexander; Brueck, Benedikt; Riess, Lukas; Hartl, Stefan; Tesche, Christian; Ebersberger, Ullrich; Wankerl, Michael; Dorwarth, Uwe; Hoffmann, Ellen (Frontiers in Cardiovascular Medicine, 2021)
Background: Cryoballoon ablation is established for pulmonary vein isolation (PVI) in paroxysmal atrial fibrillation (AF). The objective was to evaluate CBA strategy in consecutive patients with persistent AF in the initial AF ablation procedure. Material and Methods: Prospectively, patients with symptomatic persistent AF scheduled for AF ablation all underwent cryoballoon PVI. Technical enhancements, laboratory management, safety, single-procedure outcome, predictors of recurrence, and durability of PVI were evaluated. Results: From 2007 to 2020, a total of 1,140 patients with persistent AF, median age 68 years, underwent cryoballoon ablation (CBA). Median left atrial (LA) diameter was 45 mm (interquantile range, IQR, 8), and Congestive heart failure, Hypertension, Age ≥75 years (doubled), Diabetes mellitus, prior Stroke or TIA or thromboembolism (doubled), Vascular disease, Age 65 to 74 years, Sex category (CHA2DS2-VASc) score was 3. Acute isolation was achieved in 99.6% of the pulmonary veins by CBA. Median LA time and median dose area product decreased significantly over time (p < 0.001). Major complications occurred in 17 (1.5%) patients including 2 (0.2%) stroke/transitory ischemic attack (TIA), 1 (0.1%) tamponade, relevant groin complications, 1 (0.1%) significant ASD, and 4 (0.4%) persistent phrenic nerve palsy (PNP). Transient PNP occurred in 66 (5.5%) patients. No atrio-esophageal fistula was documented. Five deaths (0.4%), unrelated to the procedure, occurred very late during follow-up. After initial CBA, arrhythmia recurrences occurred in 46.6% of the patients. Freedom from atrial arrhythmias at 1-, and 2-year was 81.8 and 61.7%, respectively. Independent predictors of recurrence were LA diameter, female sex, and use of the first cryoballoon generation. Repeat ablations due to recurrences were performed in 268 (23.5%) of the 1,140 patients. No pulmonary vein (PV) reconduction was found in 49.6% of the patients and 73.5% of PVs. This rate increased to 66.4% of the patients and 88% of PVs if an advanced cryoballoon was used in the first AF ablation procedure. Conclusion: Cryoballoon ablation for symptomatic persistent AF is a reasonable strategy in the initial AF ablation procedure.